Manipulation of frozen water droplets with nano-particles - Khiew, Kian Sin (2018)
The freezing of water droplets has been a topic of interest in the research world for many years as understanding of it offers numerous benefits such as better thermal energy storage method and helps to improve aircraft anti-icing strategy. However, the detailed mechanism of this solidification process is still not well understood especially under the presences of air bubbles. The aim of this project is to determine how contact angle can affect the bubble state in a frozen water droplet and to study the effect of air bubbles of different position and sizes have on water droplet ice formation process. The mechanism of this water droplet frozen process is to be microscopically examined in term of freezing rate and bubble state through a sCMOS technology enabled camera attached to a microscope on the customized test rig. It has been found that larger contact angle tends to promote the freezing of the induced bubble in water droplet while smaller contact angle is likely to cause the bubble to break upon freezing complete. As for the freezing rate of bubbled induced water droplets, the freezing time reduces dramatically when the volume of the induced bubble is reduced. Large induced bubble however, does not seem to affect the freezing rate in any significant way.